DOPPLER INDICES OF UMBILICAL ARTERY, UTERO-PLACENTAL ARTERY AND FETAL AORTA DURING NORMAL GESTATION IN BITCHES - UMAMAGESWARI, J; SRIDEVI, P; JOSEPH, C (The Indian Journal of Animal Reproduction, 2022)
Twelve pregnant bitches of different breeds were examined at weekly interval, from fifth week of gestationonward, to determine changes in blood flow of umbilical artery, utero-placental artery and fetal aorta. Dopplerultrasonography aided alterations in doppler indices viz. peak systolic velocity (PSV), end diastolic velocity (EDV),pulsatility index (PI) and resistance index (RI) of above vessels were assessed. The umbilical and uteroplacentalarteries of pregnant bitches and the abdominal aorta of fetuses showed progressive increase in PSV and EDV(p
Keywords: Bitches; Blood flow; Canine; Doppler ultrasound; Pregnancy